2015
DOI: 10.1002/ldr.2387
|View full text |Cite
|
Sign up to set email alerts
|

Relative Contribution of Rill/Interrill and Gully/Channel Erosion to Small Reservoir Siltation in Mediterranean Environments

Abstract: Reservoir siltation because of water erosion is an important environmental issue in Mediterranean countries where storage of clear surface water is crucial for their economic and agricultural development. The high density of gully systems observed in Mediterranean regions raises the question of their contribution to reservoir siltation. In this context, this study quantified the absolute and relative contributions of rill/interrill and gully/channel erosion in sediment accumulation at the outlet of small Tunis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 64 publications
0
51
0
Order By: Relevance
“…Ben Slimane et al . () found that sheet and rill erosion rates were 20–80% of the total erosion rates for catchments in semi‐arid Tunisia. Thus, the PESERA‐based sediment yield at the check‐dam could be in the range of 1·5–6 Mg ha −1 y −1 .…”
Section: Resultsmentioning
confidence: 99%
“…Ben Slimane et al . () found that sheet and rill erosion rates were 20–80% of the total erosion rates for catchments in semi‐arid Tunisia. Thus, the PESERA‐based sediment yield at the check‐dam could be in the range of 1·5–6 Mg ha −1 y −1 .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, sparse vegetation, soil sealing, and crusting decrease the potential infiltration capacity of the soils in many areas Belaid & Habaieb (), leading to a predominant surface runoff response and thus accelerating soil erosion. The high susceptibility to water erosion of the dry Mediterranean environments is well known (Raclot et al, ; Laudicina et al, ) and seems particularly valid for the Tunisian landscape (Hermassi et al, ; Ben Slimane et al, ).…”
Section: Introductionmentioning
confidence: 98%
“…Studies in watersheds under agricultural production, using fingerprinting technique for source identification of sediment transported in suspension, have been conducted successfully in several countries and have been expanding rapidly (Slimane et al, ; Smith et al, ). Studies were carried out in small rural watersheds in Southern Brazil, in sloping areas cropped mainly with tobacco in small family‐farm units (Minella et al, ; Minella et al, ; Minella, Merten, & Clarke, ; Minella, Merten, Walling, et al, ; Tiecher, Caner, Minella, Bender, et al, ; Tiecher, Caner, Minella, & Santos, ), for no‐till annual crops (Tiecher et al, ), on hillsides with shallow soils and non‐intensive agriculture (Miguel, Dalmolin, Pedron, & Moura‐Bueno, ; Miguel, Dalmolin, Pedron, Moura‐Bueno, & Tiecher, ), and for urban watersheds (Franz, Makeschin, Wei, & Lorz, ; Poleto, Merten, & Minella, ).…”
Section: Introductionmentioning
confidence: 99%